250 års Juelehjælp. Den Iuelske Stiftelse i Algade og Klostervang 1761-2027 - Zeuner, Jakob (Historisk Årbog for Roskilde Amt, 2026)
250 års Juelehjælp. Den Iuelske Stiftelse i Algade og Klostervang 1761-2027